Between Modernization and Marginalization: A Historical Analysis of Colonial Health Policies in Semarang and Their Postcolonial Legacy - Endah Sri Hartatik; Wasino; Vivek Neelakantan; Sukarni Suryaningsih; Ken Widyawati; Ilham Nur Utomo; Fortuna Devi Putri Sina (istory Department, Faculty of Social Sciences, Universitas Negeri Semarang in collaboration with Masyarakat Sejarawan Indonesia (Indonesian Historical Society), 2025)
Abstract: This article examines the population health policies implemented in Semarang City, Indonesia, in the aftermath of the Dutch colonial Ethical Policy (1901). Employing a social determinant of health framework grounded in a decolonial perspective, the study explores how colonial era policies continue to shape contemporary health practices and reinforce structural health inequalities. Drawing on historical methods and analysis of primary and secondary sources from national archives, libraries, and documentation centers, the research finds that the Ethical Policy—despite its humanitarian rhetoric of